POLITIK IDENTITAS (Suatu Kajian Awal Dalam Kerangka dan Interaksi âLokalitasâ dan âGlobalisasiâ) - Sukamto, Sukamto (Jurnal Sejarah dan Budaya, 2010)
Abstract: Identity was significant into human live, social life and prior to state life. By means of Identity, we can identify and make differenciate between peoples. Furthermore, we can stratified occupations with identity. Identity arise wihout any falseness but it most engaging with dominance so identity appear as a politic identity. Politic Identity becoming part from social defensive to get existence and hegemony in private or public area. It shows in many ways, such as organization symbols, flags, and any signs that significantly differ from others.